Barangay Assembly: A Citizen-Led Reinvigoration of Political Discourse and Civic Engagement in the Philippines - Yusingco, Michael Henry (Archīum Ateneo, 2022)
The Filipino indigenous custom of collective action known as bayanihan is institutionalized in the Barangay Assembly; a community forum where citizens can directly influence local governance. However; it is not widely utilized because many barangay officials are co-opted by local political dynasties. Results of the 2019 elections reveal that political dynasties continue to dominate the electoral process; making genuine political competition virtually impossible. This piece will present the strategy of using the Barangay Assembly as a citizen-led reinvigoration of political discourse and civic engagement. It will expound on the inherent value of the Barangay Assembly as a venue for purposeful democratic deliberation at the community level and the suitability of actively involving civil society organizations (CSOs) in organizing and managing those deliberative sessions. The piece will make the argument that citizens can collectively exert more influence in local politics and governance by routinely utilizing the Barangay Assembly in this manner. This regular formal process of robust civic participation in local democracy can then instigate the incremental erosion of political dynasty domination in local politics.